Prosthetic rehabilitation on patient with orbital defect: A customised approach - Idris, Rostam Iffendi; Tengku Mohd Ariff, Tengku Fazrina (IIUM Journal of Orofacial and Health Sciences, 2023)
Loss of eye leads to significant psychological trauma which necessitate rehabilitation. Restoring eye defects with prostheses will uplift psychological status of such patients by re-establishing the facial structures and appearance, eventually returning them to their normal life. Even though prefabricated orbital prostheses are available, the lack of proper fitting indirectly affect comfort and aesthetics. Custom-made orbital prosthesis is still preferred due to its conformity which correspond to individual defect and the ability for shade personalization. This article elaborates the technique of fabrication of a custom-made orbital prosthesis in giving a life-like appearance to the patient.